Kajian pemikiran Badiuzzaman Said Nursi terhadap kenabian berdasarkan kitab Rasail an-Nur / Muaz Hj Mohd Noor … [et al.] - Hj Mohd Noor, Muaz (2015)
This study is an attempt to elaborate on metaphysical thinking of a mujaddid, a highly influential intellectual and reformer of the 20th century, Sheikh Badiuzzaman Said Bin Mirza (Said Nursi) on the question of prophethood. This study gives emphasis on several key concepts associated with the prophetic nature, such as the concept of divinity, miracles, and importance messages of the prophet. This study focuses on the great books of Said Nursi, Rasāil an-Nūr, which is sourced from the al-Qurān and al-Hadith. For further interpretation of each debate, the author has presented an overview of some 'scholars' of various schools of thought as a comparison. From the aspect implementation of the study, the authors have adopted the use of documentation to gather all the necessary data, while the method of inductive, deductive and comparative is used to analyze all the data collected. The findings of this study show that prophecy is an important issue and so fundamental in Islam. This is because through their intercession Islam is erected today. Said Nursi appears to have proved that the prophetic style of thinking can solve the issue of the community that exist on this day, though the prophecy has passed over 1400 years ago.